2013
DOI: 10.1371/journal.pone.0053411
|View full text |Cite
|
Sign up to set email alerts
|

Cancer Incidence and Mortality in Patients with Type 2 Diabetes Treated with Human Insulin: A Cohort Study in Shanghai

Abstract: AimThe aim was to investigate the association between human insulin and cancer incidence and mortality in Chinese patients with type 2 diabetes.MethodsWe recruited 8,774 insulin-naïve diabetes patients from the Shanghai Diabetes Registry (SDR). The follow-up rate was 85.4%. All subjects were divided into the insulin use cohort (n = 3,639) and the non-insulin use cohort (n = 5,135). The primary outcome was the first diagnosis of any cancer. The secondary outcome was all-cause mortality. Cox proportional hazards… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(27 citation statements)
references
References 21 publications
0
27
0
Order By: Relevance
“…Diabetes mellitus has been associated with a decreased risk of lung cancer in some (Rousseau et al, 2006;Ogunleye et al, 2009;Atchison et al, 2011) but not all studies (Hall et al, 2005;Ehrlich et al, 2010;Lai et al, 2012), a finding which may be explained by different smoking habits. Furthermore, it was reported that diabetic patients using metformin plus any other treatment had a lung cancer risk that was 37% lower than those not using the anti-diabetes drug (Hall et al, 2005).…”
Section: Anti-diabetic Medications Do Not Influence Risk Of Lungmentioning
confidence: 93%
See 3 more Smart Citations
“…Diabetes mellitus has been associated with a decreased risk of lung cancer in some (Rousseau et al, 2006;Ogunleye et al, 2009;Atchison et al, 2011) but not all studies (Hall et al, 2005;Ehrlich et al, 2010;Lai et al, 2012), a finding which may be explained by different smoking habits. Furthermore, it was reported that diabetic patients using metformin plus any other treatment had a lung cancer risk that was 37% lower than those not using the anti-diabetes drug (Hall et al, 2005).…”
Section: Anti-diabetic Medications Do Not Influence Risk Of Lungmentioning
confidence: 93%
“…Furthermore, it was reported that diabetic patients using metformin plus any other treatment had a lung cancer risk that was 37% lower than those not using the anti-diabetes drug (Hall et al, 2005).…”
Section: Anti-diabetic Medications Do Not Influence Risk Of Lungmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, while the physiological pattern of insulin secretion to the portal vein includes degradation and utilization of a significant proportion of the hormone in the liver, exogenous administration allows higher availability of insulin to the peripheral tissues (12). However, a Chinese cohort study demonstrated that there was no excess risk of overall cancer in T2DM patients treated with human insulin, regardless of an increased overall and cancer mortality among insulin users (29).…”
Section: Diabetes Cancer and Therapiesmentioning
confidence: 99%